Application of the iPLEXTM Gold SNP genotyping method for the analysis of Amerindian ancient DNA samples: Benefits for ancient population studies - Mendisco, Fanny (2011)
Important developments in the matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) technique have generated new perspectives regarding SNP genotyping, which are particularly promising for ancient population-based studies. The main aim of the present study was to investigate the application of a MALDI-TOF MS-based SNP genotyping technique, called iPLEX® Gold, to analyze Amerindian ancient DNA samples. The first objective was to test the sensitivity of the method, which is recommended for DNA quantities between 10 and 5ng, for ancient biological samples containing DNA molecules that were degraded and present in minute quantities. The second objective was to detail the advantages of this technique for studies on ancient populations. Two multiplexes were designed, allowing the major Amerindian mitochondrial and Y haplogroups to be determined simultaneously. This analysis has never been described before. Results demonstrated the reliability and accuracy of the method; data were obtained for both mitochondrial and nuclear DNA using picogram (pg) quantities of nucleic acid. This technique has the advantages of both MS and minisequencing techniques; thus, it should be included in the protocols for future ancient DNA studies.